Antibiotic residue and toxicity assessment of wastewater during the pharmaceutical production processes. (March 2022) - Xue, JiaJia; Lei, Dandan; Zhao, Xiumei; Hu, Yaru; Yao, Shijie; Lin, Kuangfei; Wang, Zejian; Cui, Changzheng
Abstract: Various pollutants are released during pharmaceutical production processes, which is of great concern. Most studies have focused on the terminal treatment results of mixed pharmaceutical wastewater, and further research on wastewater from the production processes is required. This study investigated the wastewater quality indicators, residual antibiotics, and biological toxicity of the wastewater during the production process in a large pharmaceutical producing factory in Northern China. The wastewater contained numerous organic pollutants, with the chemical oxygen demand (COD) values ranging from 2.0 × 10 3 to 2.6 × 10 5  mg L −1 and the total nitrogen (TN) values ranging from 1.3 × 10 3 to 2.0 × 10 4  mg L −1 . High concentrations of cephalexin and cefradine remained in the wastewater of the production workshop, with the highest concentration of cefradine reaching 1328 mg L −1 . The wastewater from the oxidation and solvent recovery workshops was more toxic to Vibrio fischeri and Daphnia magna than that of other workshops. Moreover, the biological acute toxicity of wastewater was significantly correlated with the concentration of COD and TN ( p  < 0.01). This study provides new insights into the treatment of antibiotic production wastewater, illuminating the incomplete extraction of products and the significant risk posed by pharmaceutical wastewater to the environment. Graphical abstract: Image 1 Highlights: Comprehensive analysis in the pharmaceutical production wastewater. Pharmaceutical wastewater was toxic to V. fischeri and D. magna . Antibiotics were less toxic to organisms than mixed wastewater. Biotoxicity was positively correlated with COD, TN, and TP.